A national study of choanal atresia in tertiary care centers in Canada – part II: clinical management - Josee Paradis; Agnieszka Dzioba; Hamdy El-Hakim; Paul Hong; Frederick K. Kozak; Lily H. P. Nguyen; Demitri Perera; Evan Jon Propst; Jennifer M. Siu; Monika Wojtera; Murad Husein; National Choanal Atresia Study Working Group (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background To evaluate the clinical management of choanal atresia (CA) in tertiary centers across Canada. Methods Multi-centre case series involving six tertiary care pediatric hospitals across Canada. Retrospective chart review of patients born between 1980 and 2010 diagnosed with choanal atresia to a participating center. Results The health charts of 215 patients (59.6% female) with choanal atresia (CA) were reviewed. Mean age of initial surgical repair was 0.8 months for bilateral CA, and 48.6 months for unilateral CA. Approaches of surgical repair consisted of endoscopic transnasal (31.7%), non-endoscopic transnasal (42.6%), and transpalatal (25.2%). Stents were used on 70.7% of patients. Forty-nine percent of patients were brought back to the OR for a planned second look; stent removal being the most common reason (86.4%). Surgical success rate of initial surgeries was 54.1%. Surgical technique was not associated with rate of restenosis [χ2 (2) = 1.6, p = .46]. Conclusions The present study is the first national multi-institutional study exploring the surgical outcomes of CA over a 30-year period. The surgical repair of CA presents a challenge to otolaryngologists, as the rate of surgical failure is high. The optimal surgical approach, age at surgical repair, use of stents, surgical adjuncts, and need for planned second look warrant further investigation. Graphical abstract